ISU KEKERASAN DALAM RELASI GENDER; SEBUAH ANALISIS ATAS NILAI KESETARAAN GENDER DI LINGKUNGAN SEKOLAH (STUDI KASUS DI MI CIWATIN PANCATENGAH TASIKMALAYA) - Munir, Asep (Siyasyatuna | Jurnal Hukum Tata Negara, 2023)
Gender Mainstreaming until now has become one of the themes that continues to trigger the logic of many people to discuss it. Various groups, starting from the level of institutions, practitioners, activists to thinkers, are busy raising this issue in the arena which does not only stop at the level of discourse, but also extends to the realm of policy. The popularity of this theme also extends to its context as a program that is part of the implementation of the duties and/or functions of an institution. That is why the background of this research will focus more on the issue of gender-based violence in social institutions at the basic education unit level, Madrasah Ibtidaiyyah (MI). The reason is simple, that educational institutions -with all the academic facilities in them-, are seen as supposed to be able to inflame multicultural education which is oriented towards strengthening the quality of awareness of gender equality in its students. Meanwhile, the framework in this study uses the theory of multiple movements which makes an idea an idea that metamorphoses into a movement and a process. In that context, the problems of gender-based violence in MI Ciwatin Pancatengah will be photographed in an orderly way by confronting it versus the idea of ​​gender equality which no longer stops at monologue aspects of discourse, but has transformed into a movement and processes into a comprehensive paradigm awareness in every student. which is under the auspices of MI Ciwatin, Pancatengah, Tasikmalaya. As a temporary conclusion, it seems that the idea of ​​gender equality developed by MI Ciwatin is more of a process oriented towards empowering school culture. The implementation framework is supported by 3 fundamental dimensions which are interlinked; first, equity pedagogy in the form of the spirit of equality education which is implemented either directly or indirectly; second, content integration which means the combination of multiculturalism values ​​into the existing educational structure and standards; third, knowledge construction that leads to the development of solid, broad and deep knowledge. All of this rests on one point, namely; minimize the potential for prejudice that may exist in MI Ciwatin students against all differences.